Changing epidemiology (etiology, complications) and projections of liver cirrhosis in Pakistan and beyond – A Review - Lal, Abhishek; Amjad, Aqsa; Zaidi, Samnita; Parkash, Om (Journal of the Pakistan Medical Association, 2026)
Liver Cirrhosis is a significant cause of morbidity and mortality worldwide among patients suffering from chronic liver disease. Liver cirrhosis was responsible for more than 2.4% of global deaths in 2019, with Asia-Pacific accounting for 62.6% of deaths due to liver diseases. Multiple causes are associated with the development of liver cirrhosis, but hepatitis B and C, and metabolic dysfunction-associated fatty liver disease are among the most common risk factors. However, the epidemiological trends of liver cirrhosis in terms of aetiology and complications are changing in different regions of the world. The current narrative review was planned to highlights aetiological trends, complications and future projections associated with liver cirrhosis at the global, regional (South Asia) and national (Pakistan) levels. ---Continue